Prevalence and antimicrobial susceptibility of coagulase positive Staphylococcus species from milk samples submitted to the Faculty of Veterinary Science Onderstepoort - Qekwana, Daniel Nenene (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.